2022
DOI: 10.1021/acscatal.2c01598
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Dynamics of CO2 Formation in Formic Acid Decomposition on Pt Surfaces

Abstract: The final CO 2 formation step in the decomposition of deuterated formic acid (DCOOH) on Pt surfaces is investigated using density functional theory (DFT) and ab initio molecular dynamics (AIMD) trajectories starting at the relevant transition states. The comparison of our AIMD simulations with the recent experimentally measured translational energy and angular distributions of the desorbed CO 2 led us to the conclusion that the decomposition is dominated by the DCOO* intermediate, and the observed thermal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(114 reference statements)
2
6
0
Order By: Relevance
“…85 However, the direct formate hydrolysis (HCOO − + H 2 O → H 2 + HCO 3 − ) was found to be negligible, thus the CO 2 together with H 2 production from HCO 3 − /CO 3 2− would be limited in the FA dehydrogenation. Referring to the previous report, 98 the carboxyl formation can be catalyzed by a metal site as a result of hydroxylation of the metal−support interface, but the formate intermediate would merely adsorb on the metal surface. Density functional theory (DFT) calculations suggested that the HOOC* formation has a significantly higher energy barrier than that for HCOO* formation, which is consistent with no experimental detection of adsorbed HOOC* species.…”
Section: Resultsmentioning
confidence: 78%
“…85 However, the direct formate hydrolysis (HCOO − + H 2 O → H 2 + HCO 3 − ) was found to be negligible, thus the CO 2 together with H 2 production from HCO 3 − /CO 3 2− would be limited in the FA dehydrogenation. Referring to the previous report, 98 the carboxyl formation can be catalyzed by a metal site as a result of hydroxylation of the metal−support interface, but the formate intermediate would merely adsorb on the metal surface. Density functional theory (DFT) calculations suggested that the HOOC* formation has a significantly higher energy barrier than that for HCOO* formation, which is consistent with no experimental detection of adsorbed HOOC* species.…”
Section: Resultsmentioning
confidence: 78%
“…We observed that extrapolating from the transition state to the initial bidentate adsorbed state requires the flipping of HCOO, which is consistent with previous studies on the decomposition of bidentate adsorbed HCOO on transition metals. 56 At our Pd−water interface, the flipping occurs around at a C−H distance of 1.2 Å. It might be mentioned that we discovered that the US simulation starting from the bidentate adsorbed HCOO struggles to timely capture this flipping process, which may well lead to an incorrect free energy curve obtained from umbrella integration (detailed discussion can be found in SI section 6).…”
Section: Resultsmentioning
confidence: 93%
“…After 46,56,57 Unlike at the water interface, bentadsorbed CO 2 on the gas-phase Pt(111) surface is highly unstable and rapidly desorbs, forming stable linear CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently carried out detailed classical trajectory calculations to unravel the posttransition state dynamics in the formation of the CO 2 product on Pt surfaces. 16 To gain further insights into the decomposition of formate, we present in this work an extensive theoretical study of the post-transition state dynamics on three model Cu catalyst surfaces. A major aim is to understand the impact of the surface facets on the decomposition dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the angular and translational energy distributions of CO 2 were measured. We have recently carried out detailed classical trajectory calculations to unravel the post-transition state dynamics in the formation of the CO 2 product on Pt surfaces …”
Section: Introductionmentioning
confidence: 99%